Isobaric vapor-liquid-equilibrium data measurement of toluene with ethyl acetate, n-Propyl Acetate, Iso-propyl Acetate, Iso-butyl Acetate, and Iso-amyl Acetate: experiments and modeling - Sutar, Dipak S.; Mali, Nilesh A.; Ghuge, Pravin D. (Journal of Chemical and Engineering Data, 2025)
The isobaric vapor-liquid equilibrium (VLE) data of the systems (ethyl acetate + toluene), (n-propyl acetate + toluene), (iso-propyl acetate + toluene), (toluene + iso-butyl acetate), and (toluene + iso-amyl acetate) were measured under the isobaric condition at 92 kPa using a glass dynamic recirculation apparatus. The experimental VLE data was correlated by NRTL, Wilson, and UNIQUAC activity coefficient models to account for the nonideality. The binary interaction parameters of the models were obtained by regressing the experimental data using the maximum likelihood objective function. The thermodynamic consistency of the experimental data was checked by using the Van Ness test and the infinite dilution test. Extrapolating the activity coefficient at infinite dilution was done by regressing the experimental data with an extended Redlich-Kister equation. The NRTL, Wilson, and UNIQUAC models exhibited a maximum root-mean-square deviation less than unity for temperature and vapor mole fraction. Additionally, it is worth noting that no azeotrope was identified in the VLE data in this study.